Nutritive and Anti-nutritive Evaluation of Cnidoscolus aurifolia Leaves - Uwemedimo Emmanuel Udo; Akaninyene Uwemedimo Udo (Turkish Journal of Agriculture: Food Science and Technology)
The leaves of Cnidoscolus aurifolia were analysed for their chemical, antinutrients, proximate and mineral element compositions using standard procedures. Phytochemical screening revealed the presence of alkaloids, saponins, flavonoids, terpenes and tannins while anthraquinones, glycosides and phlobatannins were absent. Proximate analysis indicated high protein content (59.45 ± 0.07%) with crude fibre and fat also present in appreciable quantities. Mineral elements determination showed the presence of calcium, iron, magnesium, potassium and zinc. Antinutrient analysis of the leaf extract of C. aurifolia indicated low levels of phytic acid and hydrocyanide well below the lethal doses. An unusually high oxalate level of 404.80 ± 0.11 mg/100 g (dry weight) was also obtained although still below toxic level. These results support the ethnomedicinal and nutritional uses of this plant and suggest that the consumption of leaves of C. aurifolia is not harmful nutritively.